Spatiotemporal evolution of landscape ecological risk and its driving factors of the Beijing–Tianjin–Hebei major mineral belt, 1985–2022 - Yilin Wang; Xiaohong Wang; Wei Zhang; Weidong Man; Mingyue Liu; Linlin Jiao (Scientific Reports)
Abstract The Beijing-Tianjin-Hebei major mineral belt represents a significant economic development area in China. Effective monitoring and assessment of the regional landscape ecological risk can provide a scientific basis for an ecological protection strategy for the environmental protection of the Beijing-Tianjin-Hebei major mineral belt. In this study, a landscape ecological risk index was constructed based on land use/land cover, and the spatial and temporal variations of landscape ecological risk were subsequently analyzed. Furthermore, the contribution of the main driving factors of landscape ecological risk was quantified in the Beijing-Tianjin-Hebei major mineral belt. The results demonstrate that: (1) The land use types within the study area underwent significant changes from 1985 to 2022. The predominant type of transfer was cropland, which was primarily converted to construction land, grassland, and woodland. (2) The landscape ecological risk in central-northern and western parts of the Beijing-Tianjin-Hebei major mineral belt is higher, while the landscape ecological risk in the southwest parts is lower. Using 2015 as the time point, the landscape ecological risk in the study area was found to change, with the average value of landscape ecological risk for all classes of landscape ecological risk within 2015–2022 being lower than that of 1985–2015, with the exception of the high-risk area. The mean annual landscape ecological risk is obviously higher during the 1985–2015 period in comparison to the 2015–2022 period, with the exception of regions exhibiting high risk. (3) There is a significant positive spatial correlation between landscape ecological risks in different periods. The pattern of landscape ecological risk exhibits both ‘high-high’ aggregation and ‘low-low’ aggregation. The ‘high-high’ aggregations are primarily located in the northern, central and western parts of the study area, while the ‘low-low’ aggregation zones are mainly located in the southeastern study region. (4) The spatial distribution of landscape ecological risk is predominantly shaped by population density and slope. In the context of interactive factor detection, the positive interaction between slope and average annual temperature, night-time illumination and slope, population density and annual precipitation were identified as exerting a more significant influence on the observed spatial differentiation of landscape ecological risk. It was found that the interaction of multiple drivers had a more pronounced impact on landscape ecological risk than any single factor. The findings of the research project provide a scientific rationale and reference for future land use, resource optimization, landscape ecological risk differential management and ecological restoration. Furthermore, the findings are of considerable importance in terms of maintaining ecological security patterns.